(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This scientific article analyzes the level of transparency in the activities of state bodies, the mechanisms and key factors for ensuring it. It is emphasized that the establishment of a dialogue between the people and the state is important in the formation of a democratic legal state and an open civil society. The tendencies of participation of non-governmental non-profit organizations in these processes have been scientifically studied.